2022
DOI: 10.37433/aad.v3i2.187
|View full text |Cite
|
Sign up to set email alerts
|

How does the public discuss gene-editing in agriculture? An analysis of Twitter content

Abstract: As people form their opinion about gene editing applications in agriculture, they are utilizing social media to seek and share information and opinions on the topic. Understanding how the public discusses this technology will influence the development of effective messaging and practitioner engagement in the conversation. The purpose of this study was to describe the characteristics of Twitter content related to applications of gene editing in agriculture. Social media monitoring facilitated a quantitative, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“… 70 , 71 ] and social media [e.g. 72 , 73 ], but never directly assessed what sources participants refer to when provided the opportunity.…”
Section: Discussionmentioning
confidence: 99%
“… 70 , 71 ] and social media [e.g. 72 , 73 ], but never directly assessed what sources participants refer to when provided the opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…Social media also plays a significant role in shaping public opinion of gene-edited foods. Analyzing discussions surrounding gene editing technologies in agricultural contexts on both social media as well as news media in the United States, Hill et al (2022) observed that tweets considerably influence public sentiment. Similarly, Tabei et al (2020) examined Twitter conversations in Japan concerning genome-edited foods and highlighted the use of social media as a tool for monitoring public interests and opinions in real-time.…”
Section: Previewmentioning
confidence: 99%
“…Consumer acceptance is necessary for the technology to maximize impact on both production and human health [MacFie, 2007]. American adults have reported GET has initial support in the context of research into direct human genetic modification in a therapeutic or preventative context [Weisberg, Badgio & Chatterjee, 2017], and a Twitter analysis from 2018-19 indicated high engagement and general positivity toward gene editing in agriculture, suggesting positive attitudes among those users [Hill, Meyers, Li, Doerfert & Mendu, 2022]. We can learn from U.S. public opposition to current genetic engineering technology, a broader category that includes GET, to improve communication and education that will positively influence consumer perception.…”
Section: Introductionmentioning
confidence: 99%